Discovery of the genus Lebioderus (Coleoptera, Carabidae, Paussinae) from China, with description of two new species - Song, Xiao-Bin; Maruyama, Munetoshi; Peng, Zhong (Zootaxa, 2017)
The rare paussine genus Lebioderus Westwood, 1838 is reported from China for the first time, based on two new species, L. sinicus Song & Maruyama sp. nov. and L. maolanus Song & Maruyama sp. nov. The type series of L. sinicus was collected from nests of Carebara Westwood, 1840 ants, which is also a first host record for Lebioderus.